Relationship Investigation of the Effect of Multi-Directional Leadership Origins on Social Intelligence - Kemal Sargin, Mesut Güleşce, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: The aim of this research is to examine the relationship between the multidimensional leadership orientations of individuals working in the Ministry of Youth and Sports and social intelligence. Aim:. Could there be a difference between different variables in the relationship between the multi-faceted leadership orientations and social intelligence levels of individuals working in the Ministry of Youth and Sports? Methods: Research method was used in our study. It was made with a descriptive scanning model. The universe of the study consists of sports managers who have worked and are working in the Ministries of Youth and Sports throughout Turkey. The sample of the research was the voluntary participation in the online survey, which was sent by e-mail to 507 people working in the sports management service at the Ministries of Youth and Sports. "Tromso Social Intelligence Scale", which he adapted to1 "Multidimensional Leadership Orientations Scale" was used. SPSS 25. Program was used in the analysis of the data. Results: According to the statistical results of the data obtained, there was a significant difference between the variables of age, working year and education level, and at the same time, there was a positive relationship between age, working year, education level, intelligence and leadership. Conclusion: Leadership orientation and social intelligence level increase with age. In addition, it is believed that the level of leadership and social intelligence increases as the education level increases.